Access to surgical assistance: challenges and perspectives - Maria Fernanda do Prado Tostes; Eduardo Rocha Covre; Carlos Alexandre Molena Fernandes (Universidade de São Paulo, 2016)
Objective to characterize the access to surgical assistance in Brazil. Method documentary study, with a quantitative approach, developed from information of the Caixa Preta da Saúde [Health Black Box] database, of the Brazilian Medical Association. Results in the one-year period 3773 cases related to health care in Brazil were recorded. There were 458 (12.3%) records on surgical assistance. Of these, most, 339 (74.1%), involved the lack of access in all regions of Brazil. The main access constraint was the prolonged waiting time for surgery. Other constraints were the excessive waiting for medical appointment with experts, doing examinations and cancellation of surgeries. Conclusion the access to surgical assistance, by users of the Brazilian health system, is not widely guaranteed, reinforcing the need for integrated governmental actions, organization of the health care network, management of health care and human resources to overcome the challenges imposed to achieve the Universal Access to Health and Universal Health Coverage.